Pengembangan Perangkat Pembelajaran Metode Brainstorming Materi Teknologi Ramah Lingkungan untuk Meningkatkan Hasil Belajar IPA Siswa - Mohammad Walid Syaifullah (IKIP Mataram, 2016)
This study aims to produce a science learning tool that is valid, practical, and effective using brainstorming methods on environmentally friendly material to improve the science learning outcomes of junior high school students. The learning tool was tested on 30 students of Class IX-B of SMP Ma’arif NU 2 Karang Penang Sampang in the academic year 2016/2017. This research is development research, with a 4-D model. The device trial design uses one group pretest-posttest design. The results of the study show: (1) the validity learning devices are categorized as valid; (2) the implementation of the lesson plan is categorized as good; Student activity shows student-centered learning; (3) positive student responses to the learning process, the average score of completeness of student learning achievements is 78.06%. Based on the results and discussion of the research, it can be concluded that science learning devices use environmentally friendly material technology brainstorming methods to improve SMP students' learning achievements are valid, practical, and effective use in learning.